Influences of Phosphoric acid (H3PO4) solution on formation of Porous Anodic Aluminum Oxide (AAO) thin film - Norul Fatihah Abdul Hadi (Universiti Malaysia Perlis, 2009)
The main objective of this study is to analyze the effect of anodizing parameter focusing on anodizing voltage and phosphoric acid (H3PO4) concentration on the formation of porous anodic aluminum oxide (AAO) film. The aluminum foils were first annealed at 500 0C for two (2) hours and cleaned by acetone degreasing, ultrasonic cleaning and alkali etching (NaOH) which were done in sequent. The first parameter studied which was the anodizing voltage effect, was done by running a number of anodizing process at different voltage ranging from 30.0V to 150.0V in 0.4M of phosphoric acid (H3PO4). Then, the study of second parameter effect was done by anodizing aluminum foils in various H3PO4 concentrations in the range between 0.05M and 3.0M with constant 50.0V anodizing voltage and 0.025A electrical current along the anodizing process. The pore diameter was found to be depending on anodizing voltage, H3PO4 concentration and also current flow as well as the electrolyte temperature. Higher voltage temperature leads to wider pore diameter while only in the 3.0M H3PO4 concentration pores were observed.